National Longitudinal Studies of Kindergarten Children: Historical Context and Ongoing Contributions. (27th March 2017) - West, Jerry
The introduction to this Special Topic Collection has two parts. To provide background and context for the articles in the collection, Part 1 tells the story of the Early Childhood Longitudinal Study program at the National Center for Education Statistics. It offers an abridged history of this program and describes the designs of the two national kindergarten cohort studies (ECLS-K and ECLS-K:2011) whose data were analyzed by the authors of each of the articles. Part 2 provides a brief overview of the five articles. It includes a summary of key findings from the articles and important patterns in the data. It highlights areas that have improved over the past decade and areas with little improvement. Limitations of the findings that are directly connected to the ECLS-K and ECLS-K:2011 designs are identified as well as other design limitations that have implications for future data users.